We Are Coming, Unafraid: The Jewish Legions and the Promised Land in the First World War - Keren, Michael; Keren, Shlomit (Rowman & Littlefield Publishers, 2010)
This book tells the little-known stories of three all-Jewish battalions formed in the British army as part of the Allies' Middle East campaign, recruiting soldiers from the United States, Canada, England, and Argentina. Many of the soldiers, ranging widely in education level, social class, and combat experience, were displaced immigrants or children of such immigrants. Together, they coalesced into the all-Jewish battalions: "the liberators of the Promised Land." The ranks of the Jewish Legions included some who would become prominent leaders, such as David Ben-Gurion, Israel's first prime minister, and Yitzhak Ben-Zvi, Israel's second president; however, this book focuses on the experiences of ordinary soldiers who served alongside them. Drawing on diaries, memoirs, and letters, the book follows their journey at sea through unrestricted submarine warfare; by trains and trucks through Europe, Egypt, and Palestine; and their battlefield experiences. The authors show how these Yiddish-speaking young men forged a new kind of soldier identity with unique Jewish features, as well as an evolving sense of nationalism.